2011
DOI: 10.1080/01441647.2010.547635
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Efficiency at Major Brazilian Port Terminals

Abstract: This paper reports on the use of different approaches for measuring the efficiency of major Brazilian port terminals. Two of the most important approaches, DEA (Data Envelopment Analysis) and SFA (Stochastic Frontier Analysis), were performed on data collected from 25 terminals. The findings indicate that the majority of Brazilian terminals are running short on capacity due to the export boom that has occurred over the past few years and due to the lack of investment in capacity expansion. Furthermore, efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 69 publications
2
28
0
Order By: Relevance
“…For example, Wanke et al (2011) also used SFA to cross-check efficiency scores with DEA results, corroborating earlier studies that found that operational inefficiencies are not purely derived from random noise. More recently, Caillaux et al (2012) used probabilistic decomposition in conjunction with DEA and the ordinal Copeland method in order to choose the most adequate transshipment port within Mercosur.…”
Section: Studies On Port Efficiency: the Brazilian Casesupporting
confidence: 74%
“…For example, Wanke et al (2011) also used SFA to cross-check efficiency scores with DEA results, corroborating earlier studies that found that operational inefficiencies are not purely derived from random noise. More recently, Caillaux et al (2012) used probabilistic decomposition in conjunction with DEA and the ordinal Copeland method in order to choose the most adequate transshipment port within Mercosur.…”
Section: Studies On Port Efficiency: the Brazilian Casesupporting
confidence: 74%
“…More precisely, according to Wanke et al . (), the basic idea behind the selection of an input‐oriented model is that the output‐increasing potential should be interpreted with more care, unless a demand for it exists. Furthermore, when selecting an input orientation, decision makers are focusing on “stressing” production inputs for a given level of output that may not necessarily be maximal, as discussed in Odeck and Alkadi ().…”
Section: Resultsmentioning
confidence: 99%
“…Latin America and Spanish ports 20052011 Mokhtar (2013) Container terminal in Peninsular Malaysia 2003Lu and Wang (2013 Major Chinese and Korean container terminals 2010 Li, and Pian (2013) Coastal container terminals in China Suárez-Alemán et al (2014) African ports 2010 Schoyen and Odeck (2013) Norwegian container ports 2002-2008Niavis and Tsekeris (2012 South-Eastern European ports 2008Bichou (2011 Container terminals 2002-2008Wanke et al (2011 Brazilian port terminals 2009 Hung, Lu and Asian container ports 2007 Cullinane and Wang (2010) 25 of the world's top container ports in 20011992Liu (2008 10 Asia-Pacific ports 1998-2001 Wang and Cullinane (2006) European container terminals 2003 Cullinane, Ji, andWang (2005) European container terminals 2003 Rios and Gastaud Maçada (2006) Container terminals in the Mercosur region 2002-2004Barros (2006 Italian ports 2002-2003Cullinane et al (2005 World's top 30 container ports 2001 Barros and Athanassiou (2004) Portuguese and Greek seaports 1998-2000 Bonilla et al (2004) Spanish port system 1995-1998 Park and De (2004) Korean ports 1999 Turner et al (2004) North American ports 1984-1997Estache et al (2004 Mexico's main ports 1996Barros (2003, 2004 Portuguese ...…”
Section: Appendixmentioning
confidence: 99%